Plurilingualism and Multiliteracies International Research on Identity Construction in Language Education - Abendroth-Timmer, Dagmar; Hennig, Eva-Maria (Kolloquium Fremdsprachenunterricht, 2014)
LANGSCAPE is a plurilingual and multicultural international research network on language acquisition and language education. The current research focus is on Identity Construction in Language Education. This volume summarizes some research results of the last four years by presenting empirical research projects as well as theoretical concepts. The contributions all deal with topics linked to plurilingualism or to certain aspects of the concept of multiliteracies like globalization, language policy, multiculturalism, multimodal communication processes, intercultural learning etc. The authors conceptualize or analyse identity construction processes of learners and educators in different plurilingual and multicultural learning environments or media based settings.